Dielectric response of disordered ferroelectrics with embedded charged clusters - Morozovska, A.N.; Eliseev, E.A.; Obukhovsky, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The model of static charged clusters, which adequately describes the dielectric hysteresis and permittivity of disordered ferroelectrics with non-isovalent impurities, has been proposed. The main result of paper is modified Landau-Ginzburg-Devonshire equation can be applied to the bulk ferroelectric materials with improper conductivity and movable charge fluctuations near the impurity centers.